An Islamic advocacy for god in the age of modernity - Abdul Razak, Mohd Abbas (Human Assistance & Development International Inc. (HADI Inc.), 2025)
In a world so divided by ideas and ideologies, and steeped in racism and class superiority, I would like to invite readers to pause and think for a moment about the crucial place that God holds in our lives, especially from an Islamic point of view. To be honest, God doesn’t need anyone to defend Him, as He is the Almighty and the Sustainer of the whole universe. As such, the purpose of this humble article is simply to remind us, and to bring us back, to the God-centred philosophy of life.